基于COSMOSWorks的三轴稳定平台框架的优化设计 - 朱有为; 聂旭涛 (Jixie chuandong)
Based on FEA of COSMOSWorks,the structure stress and model for fram of three-axis table are analysed.An optimal mathematic model is built by taking the moment of inertia of frame as objective function,the structural dimensions,stress and 1st inherent frequency as constrained condition,and the resulte is calculated correctly by COSMOSWorks.This optimal design of mechanical system of table shows that FEA optimum design plays an important role in the modern mechanical design.